A Note of the Effect of Pin-holes on Strength of Timber - Rajput, S. S.; Gupta, V. K. (Indian Forester, 1980)
Stressing the need of knowledge of effect of defects in wood on it strength and general utilisation characters, the effect of pin-holes on the bending and compressive strength of Pinus roxburghii and Shorea robusta has been studied in some detail.